The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1987
DOI: 10.1128/mcb.7.6.2046
|View full text |Cite
|
Sign up to set email alerts
|

Formation of an active transcription complex in the Drosophila melanogaster 5S RNA gene is dependent on an upstream region.

Abstract: We constructed deletion-substitution and linker-scanning mutations in the 5'-flanking region of the Drosophila melanogaster 5S RNA gene. In vitro transcription of these templates in Drosophila and HeLa cell extracts revealed the presence of an essential control region (-30 region) located between nucleotides -39 and -26 upstream of the transcription initiation site: deletion of sequences upstream of nucleotide position -39 had no detectable effect on the wild-type level of in vitro transcription, whereas mutat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

1988
1988
1998
1998

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 24 publications
(21 reference statements)
2
21
0
Order By: Relevance
“…The disruption of base pairing in the 5' stem-loop caused by substitutions in this region [e.g., clones 87U6(1-10 sub) and 87U6 (11)(12)(13)(14)(15)(16)(17)(18)(19)(20) This result is consistent with the hypothesis that the normal A block binding transcription factor TFIIIC can bind to the 87U6 A block region in the context of the 5S gene. However, this conclusion will require further experimental verification.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The disruption of base pairing in the 5' stem-loop caused by substitutions in this region [e.g., clones 87U6(1-10 sub) and 87U6 (11)(12)(13)(14)(15)(16)(17)(18)(19)(20) This result is consistent with the hypothesis that the normal A block binding transcription factor TFIIIC can bind to the 87U6 A block region in the context of the 5S gene. However, this conclusion will require further experimental verification.…”
Section: Discussionsupporting
confidence: 80%
“…The level of this transcription is approximately the same as that of the consensus U6 clone that possesses all known 5' promoter elements (pGEM/U6). However, many studies have shown an effect of flanking sequences on the transcription of genes with internal promoters (1,12,26,31 [for review, see reference 13]), and we decided to systematically investigate whether or not this is the case with 87U6. Figure 1 provides a summary of these results.…”
Section: Resultsmentioning
confidence: 99%
“…Kassavetis et al {1989} andBraun et al {1989} have shown that the analogous region of tRNA and 5S rRNA genes is bound by TFIIIB in a TFIIIC-dependent fashion. Although many tRNA and 5S rRNA genes do not exhibit a strong upstream sequence dependence, suggesting that TFIIIB can bind in a sequence-independent manner, TATA-like sequences are often present -3 0 bp upstream of tRNA and 5S rRNA genes, and, in some cases, are absolutely required for promoter function (Larson et al 1983;Selker et al 1986;Garcia et al 1987}. Furthermore, movement of the TATA-like sequence with respect to the coding region of a Neurospora 5S rRNA gene can result in a corresponding shift in the transcriptional start site {Tyler…”
Section: Implications For U6 Genes In Other Organismsmentioning
confidence: 99%
“…The 5'-and 3'-deletion mutations were used to construct linker substitution (LS) mutations as described by Garcia et al (19). 5'-and 3'-deletion fragments were ligated via the EcoRI site originally located in the polylinker of M13mp9.…”
Section: Methodsmentioning
confidence: 99%